Roberta Facchinetti (ed.), A Cultural Journey through the English Lexicon (Altre Modernità, 2013)
(Newcastle upon Tyne, Cambridge Scholars Publishing, 2012, 1 vol., 283 pp. ISBN 1-4438-3509-9)di Angela Andreani